Effect of career exploration program on career maturity and self-concept among Form Four students / Lau Poh Li - Lau, Poh Li (2011)
This study investigated the effect of the Career Exploration Program (CEP) on career maturity and self-concept of Form Four subjects (N = 139) in a typical secondary school as assessed by the Career Maturity Inventory Revised (CMI-R) and Tennessee Self-Concept Scale: 2nd Edition (TSCS:2). Gender was another independent variable examined in this study. The study was designed to determine if the level of career maturity and self-concept enhanced via the CEP treatment can be retained after 4 weeks. The students’ evaluation on CEP was also investigated. This study utilized true experimental (pretest/post-test, control group) design. The CEP was carried out over 8 consecutive weeks; the group met weekly for around one and a half hours. The CEP was divided into 5 stages: self-knowledge, career knowledge, educational information, career goals, and career plans. The findings showed that the CEP treatment had enhanced the career maturity and self-concept of the experimental subjects and that the level of career maturity and self-concept (increased via the) could be retained after a period 4 weeks. The findings also indicated that the CEP had enhanced the career maturity and self-concept of both male and female students. The results of the students’ evaluation in the CEP appeared to be satisfactory. The findings of this study indicated that the CEP could enhance the students’ career maturity and self-concept. This study has significant implications for career guidance and counseling practice with a school context in Malaysia.